Chloride penetration resistance of concrete sealer and coating systems - Soudki, Khaled A.; Safiuddin, Md.; Jeffs, Paul; Macdonald, Gary; Kroker, Marcos (Journal of Civil Engineering and Management, 2015)
This study investigated the chloride penetration resistance of a silane-based sealer (SS1), an acrylic-based coating (AC1), and two cementitious coatings (CC1 and CC2) when applied on concrete surface. Concrete powder samples were collected from 15, 30 and 45 mm depths of sealer and coating treated concrete prism specimens, which were exposed to H2O and de-icing solutions of NaCl, Geomelt S30, MgCl2 and CaCl2 for 100 freeze-thaw cycles followed by 25 wet-dry cycles. Chloride analysis was carried out to determine the total water-soluble chlorides of concrete. Test results revealed that the chloride penetration for exposure to the de-icing chemicals occurred at a depth of 15 mm from the concrete surface. The highest chloride penetration occurred for the non-treated concrete. The sealer ‘SS1’ exhibited good performance except with exposure to NaCl solution. Among the three different coating products, the acrylic-based coating ‘AC1’ was the best-performing coating, whereas the cementitious coating ‘CC1’ had the worst performance. The amount of penetrated water-soluble chlorides was greater than the maximum recommended value of 0.025% (by concrete weight) at 15 mm depth for the sealer ‘SS1’ when exposed to NaCl de-icing solution, and for the coating ‘CC1’ when exposed to NaCl, CaCl2 and MgCl2 solutions.